Microreaction processes for synthesis and utilization of epoxides: A review. (16th January 2021) - Yan, Zifei; Tian, Jiaxin; Wang, Kai; Nigam, Krishna D.P.; Luo, Guangsheng
Graphical abstract: Highlights: Microreaction technology can intensify the reactions related to epoxides. Mass and heat transfer characteristics in catalytic microreactors. Multiphase epoxidation processes using O2, H2 O2 and hydroperoxide as oxidants. Ring-opening of epoxides by nucleophilic attack. Abstract: Microreaction process is becoming an effective approach to intensify numerous chemical reactions in the laboratory research and industrial production. In this review, the excellent characteristics of microreaction processes, including high safety, narrow residence time distribution, rapid reactant mixing, high mass and heat transfer rates and simple scale-up strategy, are embodied in the recent research progress of epoxide synthesis and utilization. Besides, the catalyst loading strategies and transfer characteristics of the heterogeneous catalytic microreactors are discussed to illustrate the essence of process intensification in microflow reactors. Finally, the strengths and further challenges are proposed to provide a perspective for the development of microreaction technology in the epoxide industry.